3D-skrivare till sjöss - En studie om möjligheten att använda additiv tillverkning ombord på fartyg - Karlsen, Rikard; Stubbe, Paul (My University, 2013)
This bachelor thesis examines and discusses the possibility of using 3D printers onboard sea going vessels. The study explores additive manufacturing where objects are built up by materials in a layer by layer principle. The basis for this work is a literature study and interviews conducted with experts in businesses and faculty in the field. This paper describes the concept of additive manufacturing (AM) and the benefits the technology provides compared to traditional manufacturing. The project shows the applications currently available in AM and potentials and problems in the field. The various techniques of AM is presented and also an examination of how the design is implemented through digital modeling. The study shows that for smaller side project, an extrusion based AM machine for plastic could be a valued tool for a committed crew. The thesis also shows that it is possible to produce spare parts onboard, but an AM system onboard is not considered to be a realistic solution regarding replacing the spare parts inventory or the crafting of tools. The thesis shows that the advantage of an AM system today is that it can offer increased availability by manufacturing parts that makes the organization less dependent on delivered parts during port visits. Moreover, it is possible that work with AM technology can be positive for ingenuity and problem solving.
Keywords: Annan teknik; Other Engineering and Technologies